Depredation Patterns of Northern Bobwhite Nest Predators in Virginia - Michael L. Fies; K. Marc Puckett (National Quail Symposium Proceedings, 2017)
Little information exists that can be used to accurately identify predator species responsible for destruction of northern bobwhite (Colinus virginianus) nests. We used remotely-tripped cameras to photograph nest predators at 25 wild bobwhite nests that were continually filled with eggs from pen-raised quail. Data describing depredation events were collected to characterize species-specific damage patterns. Seven species of nest predators were photographed 1,797 times from June to October 1996. We describe depredation patterns for opossums (Didelphis marsupialis), striped skunks (Mephitis mephitis), raccoons (Procyon lotor), gray fox (Urocyon cinereoargenteus), and domestic dogs (Canis familiaris). These descriptions should help researchers identify the predator species responsible for destroyed bobwhite nests.